2007
DOI: 10.1017/s1742758407780840
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the use of alternative capsid control methods towards sustainable production of organic cocoa in Ghana

Abstract: Cocoa (Theobroma cacao L.) is an important foreign exchange earner for Ghana. However, production is constrained by a high incidence of pests and diseases. Based on farmers' needs, this study focused on the control of capsids, mainly Sahlbergella singularis Haglund and Distantiella theobroma (Distant) (both Hemiptera: Miridae). Annual crop loss caused by capsids is estimated at 25 -30%. To control capsids, formal research recommends application of synthetic insecticides four times between August and December. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 3 publications
2
27
0
1
Order By: Relevance
“…() demonstrated that traps at 1.8 m caught 8% of the numbers of male S. singularis caught in traps positioned just beneath the canopy. Similarly low‐trap heights had been used in earlier pheromone trapping studies in cacao (Padi et al., ; Ayenor et al., ; Mahob et al., ), although, in response to the results of Sarfo (), Awudzi et al. () placed their traps at 2.7 m. Sarfo et al.…”
Section: Discussionmentioning
confidence: 98%
“…() demonstrated that traps at 1.8 m caught 8% of the numbers of male S. singularis caught in traps positioned just beneath the canopy. Similarly low‐trap heights had been used in earlier pheromone trapping studies in cacao (Padi et al., ; Ayenor et al., ; Mahob et al., ), although, in response to the results of Sarfo (), Awudzi et al. () placed their traps at 2.7 m. Sarfo et al.…”
Section: Discussionmentioning
confidence: 98%
“…However, over the years cocoa production has faced major challenges, among these is the incidence of insect pests and diseases which has been recognized as a major cause of declining yields in cocoa (Ayenor et al 2007;Ntiamoah and Afrane 2008). This has adverse consequences for the country's economy.…”
Section: Introductionmentioning
confidence: 99%
“…The weaver ant O. smaragdina in Asia and Australia has a sister species, O. longinoda, in tropical Africa, which is also an efficient biocontrol agent of the main insect pests of coconut (Way 1953;Vanderplank 1960), cocoa (Leston 1973;Ayenor et al 2007;Dejean et al 1991), mango (Van Mele et al 2007) and cashew (Dwomoh et al 2009). Both insect species are similar in their foraging behaviour.…”
Section: Discussionmentioning
confidence: 99%